2016
DOI: 10.1111/opo.12283
|View full text |Cite
|
Sign up to set email alerts
|

Infrared reflectance imaging in age‐related macular degeneration

Abstract: PurposeThe purpose of this article is to describe the appearance of age‐related macular degeneration (AMD) phenotypes using infrared (IR) reflectance imaging. IR reflectance imaging of the retina has the potential to highlight specific sub‐retinal features and pathology. However, its role in macular disease, specifically AMD, is often underestimated and requires clarification.Recent findingsRecent advances in clinical methods, imaging and scientific knowledge may be integrated to improve the accuracy of diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 59 publications
0
37
1
1
Order By: Relevance
“…In contrast, GA will appear as a bright patch on the IR image due to reflection off the sclera. 50,51 Key indications: NIR is especially useful for imaging of atrophic lesions (particularly those involving the fovea centre) and reticular pseudodrusen. See Figure 2B.…”
Section: Near Infrared Imaging (Nir)mentioning
confidence: 99%
“…In contrast, GA will appear as a bright patch on the IR image due to reflection off the sclera. 50,51 Key indications: NIR is especially useful for imaging of atrophic lesions (particularly those involving the fovea centre) and reticular pseudodrusen. See Figure 2B.…”
Section: Near Infrared Imaging (Nir)mentioning
confidence: 99%
“…The test data set were allocated to a panel of selected graders (n = 6) who were previously certified for grading Focal, well-defined spots of hyperreflectivity with a distribution in all, areas of the fundus. 9 Focal deformation or thickening located between the basal lamina of the retinal pigment epithelium (RPE) and Bruch's membrane creating irregularities and undulations of <63 lm in diameter or less. 10…”
Section: Image Selectionmentioning
confidence: 99%
“…8 Well-demarcated, bright zones of hyperreflective regions where choroidal vessel profiles are visible. 9 A sharp edged region of increased signal transmission through the RPE/ Bruch's complex, associated with complete loss of the outer nuclear layer, RPE and underlying choriocapillaris. 13…”
Section: Reticular Pseudodrusenmentioning
confidence: 99%
See 1 more Smart Citation
“…The special issue also emphasised fundamental research questions that can be addressed with imaging. These included diurnal changes in ocular tissues, 5 the use of imaging to understand and diagnose retinal disease 3,6,7 and the extent to which the brain changes its structure and function in individuals with macular degeneration or glaucoma. 8,9 In addition, contemporary themes in vision science imaging research were identified by two invited review papers featured within the special issue.…”
mentioning
confidence: 99%